The relationship between Vitamin D status and exacerbation in COPD patients– a literature review. (June 2018) - Ferrari, Renata; Caram, Laura M.O.; Tanni, Suzana E.; Godoy, Irma; Rupp de Paiva, Sergio Alberto
Abstract: Objective: To investigate the relationship between Vitamin D and exacerbation in COPD patients. Methods: The PubMed database was searched for articles published from 2012 onwards using search terms related to Vitamin D and exacerbation in COPD patients. Meta-analysis, clinical trials, observational studies, and human studies were included. Non-English articles or articles with full text unavailable were excluded; a total of 15 articles were selected. Results: The association between exacerbation frequency and Vitamin D levels in observational studies remains controversial, however, meta-analysis revealed a negative association between serum Vitamin D and exacerbation. Also, two clinical trials showed that Vitamin D3 supplementation in COPD patients reduced the risk of moderate and severe exacerbation. Vitamin D binding protein (VDBP) polymorphisms seem to affect patient exacerbation susceptibility. Conclusions: Few studies in literature have data related to diet, 25-hydroxyVitamin D [25(OH)D] and polymorphism in COPD exacerbation. One clinical trial indicates Vitamin D supplementation plays a role in COPD patients with hypovitaminosis D in preventing exacerbations. Further studies are needed to elucidate the role of Vitamin D in this population and to establish the best marker for Vitamin D, which patient subgroups will benefit, and the best supplement dosage without leading to toxicity.